Market dynamics and structural challenges in competitiveness of bamboo in Malaysia’s wood-based industry - Kamaruddin, Norfaryanti; Al-Edrus, Syeed Saifulazry Osman; Haida, Zainol (Smujo International, 2026)
This study examines the competitiveness of bamboo within Malaysia’s wood-based industry, with particular attention to market dynamics and structural constraints influencing its industrial adoption. Using Porter’s Five Forces as an analytical framework, the study draws on structured questionnaire and semi-structured interview data from nine industry stakeholders, including manufacturers and relevant government agencies. The findings indicate high awareness of alternative raw materials among respondents, alongside a more cautious level of readiness to adopt bamboo in production. While most stakeholders recognise bamboo’s potential to complement conventional timber, fewer indicate readiness to invest in high-value engineered bamboo products. This pattern suggests that industry preparedness is shaped more by market uncertainty, investment risk, and supply-chain reliability than by technical feasibility. Analysis through Porter’s Five Forces positions bamboo as a promising yet structurally constrained competitor within Malaysia’s wood-based sector. Weak supplier power, strong buyer influence, persistent competition from established timber products, and high barriers to entry collectively limit bamboo’s competitive position. Qualitative insights further highlight challenges related to fragmented supply chains, limited certification systems, and uneven access to financing, which reduce firms’ willingness to commit to large-scale adoption. Although exploratory in nature and based on a limited sample, the study provides insight into the competitive conditions shaping bamboo’s industrial uptake in Malaysia. The findings highlight the importance of addressing structural and institutional constraints, particularly certification development, financing mechanisms, and industry–research linkages, to strengthen bamboo’s competitiveness. These insights are relevant to ongoing policy discussions under Malaysia’s National Agrocommodity Policy (2021-2030) and Biomass Action Plan (2022-2030), especially in supporting diversification within the wood-based industry.